The Effect of Baby Food E-Store Image (for Ages 0–3) on Consumers’ Purchase Intention - Jiao, Chunlan; Shen, Xiangdong; Wang, Li (Frontiers in Psychology, 2021)
This research aims to investigate the influence of baby food e-store image (for ages 0–3) on consumers’ purchase intention, mainly based on the S-O-R model. Perceived value is additionally tested as a mediator of the relationship between baby food e-store image and consumers’ purchase intention. An online questionnaire survey was conducted among consumers of baby food e-stores that specialize in ages 0–3. The final sample comprised 584 valid responses. To test the hypotheses in the relationships among latent variables, structural equation model analysis was used in this study. The findings showed that design image, order fulfillment image, communication service image, and security image of baby food e-stores have positive effects on consumers’ perceived value, while perceived value mediates the relationship between baby food e-stores and consumers’ purchase intention. As a result, more perceived value would be created between online stores and their consumers with a higher level of value. Two managerial implications derived from this study explain how to manage baby food e-stores and how to promote online baby food undertakings. In short, consumers’ perceived value of emotional value and functional value is stimulated by baby food e-store image and ultimately affects consumers’ purchase intention. The originality and value of this study enriches the importance of consumers’ perceived value in the field of online store image. Moreover, this study demonstrates that baby food e-store image increases consumers’ perceived value and purchase intention.